VD_FINDINFO HC / 2011 / 555 vom 14. Oktober 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, ENFANT, MAJORITÉ{ÂGE}, MAXIME INQUISITOIRE, MAXIME OFFICIELLE, NOUVEAU MOYEN DE PREUVE | 277 al. 2 CC, 296 CPC (CH), 317 al. 1 CPC (CH)